Cu‐Co Hybrid Crystals Assembled on Hollow Microsphere: Temperature‐Dependent Top‐Down Synthesis and Aggregation‐Induced Conversion from Microwave Shielding to Absorption. Issue 4 (27th November 2022) - Jia, Qianqian; An, Zhenguo; Li, Man; Liu, Ran; Xiao, Weixin; Zhang, Jingjie
Abstract: The construction of hollow metallic microspheres with rationally designed building blocks of the metal shell is a promising way to achieve low density and functionality control, but the microengineering of the metallic structures on a micrometer spherical surface is a great challenge. In the present work, a novel and simple calcination‐induced aggregation strategy is developed to realize the distribution status and microstructure control of Co‐Cu bimetal building blocks assembled on a hollow glass microsphere support, and thus a series of low‐density (0.58 g cm −3 ) dual shell composite hollow microspheres are constructed with gradient in electromagnetic property depending on the calcination temperature (CT). The optimized microwave shielding performance can be achieved at a CT of 500 °C, while further increasing CT to 700 °C leads to an interesting conversion from microwave shielding to absorption with an optimized effective absorption bandwidth of 4.64 GHz at a low matching thickness of 1.33 mm. The mechanism underlying the CT‐dependent metallic shell structure variation and further the decisive effect of the shell structure on the microwave response behavior are proposed based on a series of contrast experiments. Abstract : A simple yet effective calcination‐induced aggregation strategy is developed to realize the controlled reshaping of the bimetallic building units of Cu@Co@HSM hybrid hollow microspheres and thus the conversion from microwave shielding to absorption. A 80–100 dB electromagnetic shielding efficiency and an effective microwave absorption bandwidth of 4.64 GHz can be acquired by changing the aggregation status.